Diseases of the thyroid in childhood and adolescence - Krassas, Gerasimos E.; Rivkees, Scott A.; Kiess, Wieland 1958- (Karger, 2007)
This volume presents the latest global knowledge of thyroid disorders in infancy, childhood, and adolescence and represents experience and views from a panel of the world’s most renowned authorities on thyroid pathophysiology and clinical entities in the pediatric population. Both basic science and clinical aspects of thyroid disease are covered. Thyroid function, from ontogenesis and anatomy of the hypothalamic-pituitary-thyroid axis to thyroid and trace elements, is discussed. Topics include thyroid disease during pregnancy, iodine deficiency and excess, thyroid autoimmunity, hypo- and hyperthyroidism, thyroid related eye disease, and thyroid cancer.Authoritative and comprehensive, this book brings together the most current information available on the topic. It is an essential resource for pediatricians, endocrinologists, internists, neonatologists, family physicians, obstetricians and gynecologists looking for an insight into the pathophysiology, clinical presentation and treatment of thyroid disease in children and adolescents
a comprehensive source of the most current information available
Includes bibliographical references and index
Keywords: Pediatrics; Endocrinology; Internal Medicine; Neonatology; Obstetrics; Pediatric Endocrinology; Jugend; Kind; Schilddrüsenkrankheit; Aufsatzsammlung